Loss of RKIP expression during the carcinogenic evolution of endometrial cancer - Martinho, Olga; Faloppa, Carlos Chaves; Neto, Cristovam Scapulatempo; Longatto-Filho, Adhemar [UNESP]; Baiocchi, Glauco; da Cunha, Isabela Werneck; Soares, Fernando Augusto; Tavares Guerreiro Fregnani, Jose Humberto; Reis, Rui Manuel (B M J Publishing Group, 2012)
Aims Endometrial cancer is one of the most common cancers in women worldwide, but there is a lack of diagnostic markers for early detection of these tumours. The raf kinase inhibitory protein (RKIP) negatively regulates the Raf/MEK/ERK pathway, and the downregulation of RKIP is associated with tumour progression and metastasis in several human neoplasms. The aim of this study was to assess the expression levels of RKIP in endometrial cancer and determine whether this expression correlates with clinical outcome in these patients.Methods Tissue microarrays constructed using tissue samples from 209 endometrial adenocarcinomas, 49 endometrial polyps and 48 endometrial hyperplasias were analysed for RKIP expression by immunohistochemistry.Results The authors found that RKIP expression decreases significantly during malignant progression of endometrial cancer; it is highly expressed in non-neoplastic tissues (polyps 79.6%; hyperplasias 87.5%) and expressed at very low levels in endometrioid adenocarcinomas (29.7%). No correlations were observed between RKIP expression, clinicopathological data and survival.Conclusion This study demonstrated for the first time that RKIP expression is lost during the carcinogenic evolution of endometrial tumours and that the loss of RKIP expression is associated with a malignant phenotype. Functional studies are needed to address the biological role of RKIP downregulation in endometrial cancer.